Evaluating the Relationship between Ferritin and Renal Function Tests in Adult Sickle Cell Anemia Patients Who Do not Take Iron Chelating Agents - Thijeel, Karar Sabah; Thuwaini, Mahdi Murshd; Jasim, Alaa Kadhim (Medical Science Journal for Advance Research, 2025)
Background: Sickle cell anemia (SCA) patients are exposed to increased iron levels due to frequent blood transfusions and hemolysis, which can lead to organs damage. Objective: This study explored the significance of iron effects on the kidneys in SCA patients who were not taking iron chelating agents (ICA). Materials and Methods: A case-control study involved 42 patients with SCA (14-55 years), who were not taking ICA, and 50 age- and sex-matched apparently healthy individuals. Hemoglobin analysis was done by Bio-Rad D10 analyzer. Ferritin was quantitated by Roche cobas e411 analyzer; urea and creatinine were evaluated by Abbott ARCHITECT c4000 analyzer. The correlations between these biomarkers were determined using Pearson correlation. Results: Significantly higher ferritin levels in SCA patients compared to healthy controls was found (642.75±254.02 vs. 40.56±37.11 ng/mL, p = <0.001; respectively), whereas no significant difference between patients and controls was recorded in urea (p = 0.305) or creatinine levels (p = 0.192). No significant correlation was found between ferritin and urea levels (p = 0.423) or between ferritin and creatinine levels (p = 0.29). Conclusions: Iron’s effect on kidney function may be less pronounced than on other organs.